Factors influencing the provision of end‐of‐life care in critical care settings: development and testing of a survey instrument. (27th November 2014) - Ranse, Kristen; Yates, Patsy; Coyer, Fiona
Abstract Aim To develop and psychometrically test a survey instrument to identify the factors influencing the provision of end‐of‐life care by critical care nurses. Background Following a decision to withdraw life‐sustaining treatment, critical care nurses remain with the patient and their family providing end‐of‐life care. Identification of factors influencing the provision of this care can give evidence to inform practice development and support nurses. Design A cross‐sectional survey of critical care nurses. Method An online survey was developed, reviewed by an expert panel and pilot tested to obtain preliminary evidence of its reliability and validity. In May 2011, a convenience sample of critical care nurses (n = 392, response rate 25%) completed the survey. The analytical approach to data obtained from the 58 items measured on a Likert scale included exploratory factor analysis and descriptive statistics. Results Exploratory factor analysis identified eight factors influencing the provision of end‐of‐life care: emotional support for nurses, palliative values, patient and family preferences, resources, organizational support, care planning, knowledge and preparedness. Internal consistency of each latent construct was deemed satisfactory. The results of descriptive statistics revealed a strong commitment to the inclusion of families in end‐of‐life care and the value of this care in the critical care setting. Conclusion This paper reports preliminary evidence of the psychometric properties of a new survey instrument. The findings may inform practice development opportunities to support critical care nurses in the provision of end‐of‐life care and improve the care that patients and their families receive.